2002
DOI: 10.1084/jem.20011544
|View full text |Cite
|
Sign up to set email alerts
|

A Natural Killer T (NKT) Cell Developmental Pathway Involving a Thymus-dependent NK1.1−CD4+ CD1d-dependent Precursor Stage

Abstract: The development of CD1d-dependent natural killer T (NKT) cells is poorly understood. We have used both CD1d/α-galactosylceramide (CD1d/αGC) tetramers and anti-NK1.1 to investigate NKT cell development in vitro and in vivo. Confirming the thymus-dependence of these cells, we show that CD1d/αGC tetramer-binding NKT cells, including NK1.1+ and NK1.1− subsets, develop in fetal thymus organ culture (FTOC) and are completely absent in nude mice. Ontogenically, CD1d/αGC tetramer-binding NKT cells first appear in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
398
1
2

Year Published

2002
2002
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 342 publications
(431 citation statements)
references
References 68 publications
28
398
1
2
Order By: Relevance
“…Consistent with its importance as a marker of NKT maturity in mice [14][15][16], CD161 was expressed by a significantly higher proportion of NKT cells in blood compared to thymus (n=24; p<0.001) (Fig. 7).…”
Section: Differential Cd161 Expression By Thymus and Blood Nkt Cellssupporting
confidence: 64%
See 1 more Smart Citation
“…Consistent with its importance as a marker of NKT maturity in mice [14][15][16], CD161 was expressed by a significantly higher proportion of NKT cells in blood compared to thymus (n=24; p<0.001) (Fig. 7).…”
Section: Differential Cd161 Expression By Thymus and Blood Nkt Cellssupporting
confidence: 64%
“…However, studies in mice have shown that NKT cells pass through an immature NK1.1 -(CD161 -) stage of development and that most NKT cells are exported from the thymus at this immature stage, presumably to continue their maturation in the periphery [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…NFκB, T-bet, Ets1, Runx1, RORγ, Itk, Rlk, AP-1) (see Ref [4] for reviews), and co-stimulatory molecules such as CD28 and ICOS [11]. Most iNKT cells leave the thymus in an immature stage (as defined by the absence of expression of NK receptors such as NK1.1) and fulfill their terminal maturation in the periphery [12][13][14]. However, a sizeable fraction of these NK1.1 − iNKT cells in the peripheral organs do not acquire expression of NK markers and in fact represent mature cells that are functionally distinct from their NK1.1 + thymic counterpart [15λ] (see below).…”
Section: What Does It Take To Make An Inkt Cell?mentioning
confidence: 99%
“…Va14i NKT cells, which can be either CD4 + or CD4 -CD8 -double negative (DN), are a thymus-dependent population derived from CD4 + CD8 + double-positive (DP) thymocytes [7][8][9][10][11]. Different maturation stages of developing thymic Va14i NKT cells have been described, characterized by the sequential acquisition of CD44 and NK1.1 in C57BL/6 mice [12][13][14]. Unlike conventional MHC-dependent T cells, Va14i NKT cells are not positively selected by thymic epithelial cells but rather by hematopoietic cells [2,[15][16][17][18], in particular by CD1d-expressing DP cortical thymocytes [19,20], which alone are sufficient for positive selection of Va14i NKT cells [21,22].…”
Section: Introductionmentioning
confidence: 99%